PYROXENITE VEINS WITHIN SSZ PERIDOTITES – EVIDENCE OF MELT-ROCK INTERACTION (EGIINGOL MASSIF), MAJOR AND TRACE ELEMENT COMPOSITION OF MINERALS - A. A. Karimov; M A. Gornova; V. A. Belyaev (Геодинамика и тектонофизика)
Evidence of melt-rock reaction between suprasubduction zone (SSZ) peridotites and island arc boninititc and tholeiitic melts are identified. This process is the cause of replacive dunites and pyroxenite veins forming, which are represent the ways of island-arc melts migration. The peridotite-melt interaction is confirmed by compositional features of rocks and minerals. Influence of boninitic melt in peridotites of South Sandwich island arc leads to increasing of TiO2 and Cr-number (Cr#) in spinels [Pearce et al., 2000] e.g. REE patterns of clinopyroxene from Voykar are equilibrium to boninitic melts [Belousov et al., 2009]. We show that pyroxenites are formed sequential, orthopyroxenites are originated firstly, websterites – after, and the main forming process is interaction of SSZ peridotites with percolating boninite-like melts.